Scalable VoIP mobility integration and deployment - Epstein, Joseph (Newnes/Elsevier, 2009)
Provides practical advice on breaking down the implementation and deployment of voice mobility networks within the office, across the campus, and on the road. Offers a complete primer on enterprise-grade Wi-Fi networking for voice mobility at scale, whether as a single-mode or dual-mode network, including information on the newest 802.11n standard and how these standards directly impact voice mobility. Includes methods of integrating existing or new VoIP networks with 3G+, CDMA 2000, WCDMA, HSPA, and WiMAX cellular networks using fixed/mobile convergence (FMC). This book provides a comprehensive examination of IP-based voice mobility, covering every step in deploying multimodal voice mobility networks. Each segment of the entire voice mobility solution is described with an eye towards the inherent problems of high-scale mobility, from wired infrastructure to end device, across multiple networks and technologies.
Keywords: Internet telephony.; Mobile communication systems.; Business communication.; elektronické knihy; electronic books